Acuerdos preferenciales de comercio en el hemisferio occidental - González Vigil, Fernando (2002)
This article analyzes the proliferation of preferential trade agreements in the Western Hemisphere, the main economic and political motivations behind them and the changes that have occurred since the sixties in integration models and countries leading the regionalism process in the hemisphere. The article scrutinizes the main achievements of this process both at the level of trade and investment flows and patterns as in terms of a convergence towards wide and stable commitments to openness and liberalization. In such a context, the evolution of FTAA negotiations is examined and relevant suggestions are made on their implications and those of bilateral or plurilateral agreements with the US regarding the building-up of the hemispheric free trade zone and its coexistence with sub-regional agreements for deeper integration, with regional trading agreements elsewhere in the world, and with the multilateral trading system.